(untitled) (Indian Journal of Case Reports, 2021)
Organophosphate (OP) poisoning is more common in developing countries such as India. Here, we report a case of self-inflicted oral OP poisoning (monocrotophos) by an adolescent male patient who presented to the emergency department of a tertiary care hospital with tachycardia and frothing without seizure episode (non-linear presentation in OP poisoning). Based on the evidence of consumption of OP compound, the management of the patient went as planned and guarded with i.v. administration of pralidoxime and atropine. Gastric lavage was done soon after the patient came to the hospital and was admitted to the Intensive care unit for 5 days and in the general ward for the next 24 h. The patient was discharged from the hospital in a hemodynamically stable state after 6 days of hospital stay by managing the cardiac, muscarinic, and nervous system events as detailed in this case report.